THE ROLE OF INTELLECTUAL CAPITAL IN KNOWLEDGE - BASED SOCIETY - Denisa-Elena Parpandel (Strategii Manageriale, 2013)
In a knowledge - based society, organizations undergo permanent changes and transformations, and the key factor of such changes is intellectual capital regarded as one of the most critical, yet most strategic values an organization might own. Analyzing intelectual capital and knowledge society over the last decades has primarily emerged in private companies, whereas at present there is an increasing concern in all the fields of activity. The goal of this paper is to emphasize the importance of intellectual capital as a source of innovation and novelty used to create competitive advantages for organizations in the era of knowledge where man must rely on intellect, intuition and creativity. The present paper is an exploratory endeavour based on the qualitative method as various information sources are resorted to in order to conceptualize the terms of intellectual capital and knowledge society: specialty literature, case studies, mass-media articles, reports of in-field organizations etc. Organizations should use all the tangible or non-tangible resources they have in order to secure their success and also to build a knowledge society which involves going a long way, based on an ample, complex process where innovation has a major role and a global nature.